Name of non-profit legal entities in Peru - Romero Antola, Mario Remo (2024)
The corporate name of non-profit legal entities in Peru is the central object of study of this article, which seeks to harmonize the legislation dispersed in our country, as well as the existing doctrine and jurisprudence in this regard, from a theoretical and practice.